2005
DOI: 10.1111/j.1398-9995.2005.00896.x
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of IgE antibodies among blood donors in Sweden and Norway

Abstract: High serum levels of IgE antibodies to various allergens are common among blood donors and the degree of sensitization and spectrum of involved allergen varies between geographical regions. Present routines to identify IgE sensitized, potential risk, donors are not satisfactory; the sensitivity of selection procedures is about 25%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 9 publications
1
39
0
1
Order By: Relevance
“…Serum samples were analysed at the Laboratory of Clinical Biochemistry at Haukeland University Hospital for serum IgE (kU/l) and IgE antibody levels by the Immuno-CAP FEIA system (Phadia, Uppsala, Sweden). Allergen-speciWc IgE was tested for the main inhalation allergens using Phadiatop ® (Dermatophagoides pteronyssinus (d1), D. farinae (d2), birch (t3), timothy (g6), mugwort (w6), cat (e1), dog (e2), horse (e3), and Cladosporium (m2)) (Johansson et al 2005). Results were assessed as negative when the total concentration of the diVerent IgE antibodies was <0.35 kU A /l (kU A = kilounits of speciWc antigen) or positive when concentration waş 0.35 kU A /l.…”
Section: Questionnairementioning
confidence: 99%
See 1 more Smart Citation
“…Serum samples were analysed at the Laboratory of Clinical Biochemistry at Haukeland University Hospital for serum IgE (kU/l) and IgE antibody levels by the Immuno-CAP FEIA system (Phadia, Uppsala, Sweden). Allergen-speciWc IgE was tested for the main inhalation allergens using Phadiatop ® (Dermatophagoides pteronyssinus (d1), D. farinae (d2), birch (t3), timothy (g6), mugwort (w6), cat (e1), dog (e2), horse (e3), and Cladosporium (m2)) (Johansson et al 2005). Results were assessed as negative when the total concentration of the diVerent IgE antibodies was <0.35 kU A /l (kU A = kilounits of speciWc antigen) or positive when concentration waş 0.35 kU A /l.…”
Section: Questionnairementioning
confidence: 99%
“…This can be performed by means of testing allergen-speciWc IgE with a mixture of common inhalant allergens such as in Phadiatop ® (Johansson et al 2005). The presence of IgE antibodies does not necessarily mean clinically active disease but have clinically predictive value for developing characteristic symptoms and to react on allergens corresponding to the speciWc IgE antibodies (Johansson et al 2004).…”
Section: Introductionmentioning
confidence: 98%
“…Allergic reactions can occur after a patient ingests or inhales these allergens. One study found that 23% of donors had significant levels of IgE antibodies to common allergens (Johansson et al, 2005a). Therefore, the risk of passive sensitization by blood and plasma transfusion is probably not low.…”
Section: Passive Sensitizationmentioning
confidence: 99%
“…In one Scandinavian study, as many as 27% of donors had IgE antibodies to 1 of 14 common allergens, which included food, medication and inhalant allergens. 5 A Canadian study found high rates of self-reported allergies among donors. 6 Theoretically, the risk of symptomatic passive transfer of IgE from transfusions would be high because of the large number of atopic blood donors.…”
Section: Key Pointsmentioning
confidence: 99%